Early-life maternal deprivation affects the mother-offspring relationship in domestic pigs, as well as the neuroendocrine development and coping behavior of piglets - Gimsa, Ulrike; Brückmann, Roberto; Tuchscherer, Armin; Tuchscherer, Margret; Kanitz, Ellen (Frontiers in Behavioral Neuroscience, 2022)
Early-life adversity may have programming effects on the psychological and physiological development of offspring. Domestic pigs (Sus scrofa) are an excellent model species for studying these effects because of their many physiological similarities to humans. Piglets from ten sows were subjected to daily two-hour maternal deprivation on postnatal days (PND) 2-15 alone (DA) or in a group of littermates (DG). Control piglets (C) from ten sows stayed with their mothers. Mother-offspring interaction, milk oxytocin, and cortisol were analyzed. An open-field/novel-object (OF/NO) test was performed with piglets on PNDs 16 and 40. Plasma cortisol and immune parameters were determined on PND 5 and 16. Two piglets from each group and sow were sacrificed on PND 20 and stress-related gene expression in the limbic system and prefrontal cortex (PFC), as well as splenic lymphocyte proliferative abilities, were examined. The milk cortisol of sows increased during the first separation of mother and offspring on the second day of lactation, whereas milk oxytocin did not change. The increase in cortisol by the OF/NO test on PND 16 was greater in C piglets than in DA and DG ones. DA piglets showed less agitated behavior than DG and C piglets in the OF/NO test at PND 16, but appeared more fearful. On PND 40, DA piglets showed more arousal than DG and C piglets in the OF/NO test. Neither plasma IgA nor N/L ratios in blood nor mitogen-induced proliferation of spleen lymphocytes were affected by deprivation. We found a higher mRNA expression of CRHR1 in the hypothalamus and a higher expression of MR in the hippocampus in DA piglets than in DG ones. The expression of GR, MR and CRHR1 genes in the PFC was reduced by maternal deprivation, however, the expression of arginine vasopressin and oxytocin receptors was not affected. Repeated maternal deprivation induces sustained effects on stress reactivity and behavior of domestic piglets. Some of these effects were buffered by the presence of littermates. In addition, we found sex-specific differences in behavior and gene expression.